Acute gonococcal arthritis: an unusual host and pathogen combination. Issue 1 (January 1995) - Lewis, D A; Pollock, L M; Randell, J; Wilson, P; Kopelman, P G
Abstract : A 76 year old man was admitted for evaluation and treatment of acute oligoarticular arthritis having recently returned from India. He was diabetic on admission. Neisseria gonorrhoeae was isolated from pus collected by arthrocentesis of his right knee and was subsequently found to be chromosomally resistant to penicillin. The isolate required proline for growth and expressed the protein 1B-1 serovar. These characteristics of host and pathogen are atypical in that gonococcal arthritis usually occurs in young women and is usually caused by N gonorrhoeae isolates exhibiting hypersusceptibility to penicillin, the arginine, hypoxanthine and uracil requiring auxotype, and the protein 1A serotype. The patient responded well to therapy with oral ciprofloxacin and initial high dose penicillin.